Clinical characteristics and prognosis of COVID-19- associated invasive pulmonary aspergillosis in critically patients: a single-center study - Xiao, Shuang; Xu, Jie; Xiao, Han; Li, Yonggang; Chen, Xu; Chen, Li; Zhao, Weifeng (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveA single-center retrospective study was conducted according to the latest diagnostic criteria of the European Consortium for Mycology in Medicine/International Society for Human and Animal Mycoses (ECMM/ISHAM) Consensus, which describes the clinical characteristics, factors influencing and prognosis of a group of patients with COVID-19 (Omicron variant) combined with invasive pulmonary mycoses with onset of disease at the end of 2022.MethodsThis study retrospectively analyzed data related to 58 hospitalized patients with severe pneumonia due to COVID-19 infection admitted to the ICU of critical care medicine, respiratory ICU, and ICU of the Department of Infections at the First Affiliated Hospital of Soochow University from December 1, 2022, to January 31, 2023. CAPA was defined according to the ECMM/ISHAM consensus criteria. Our study compared the clinical and microbiological characteristics and associated risk factors of fungal infections and pulmonary fungal infections and performed univariate and multivariate analyses of factors associated with mortality in patients with COVID-19-Associated Pulmonary Aspergillosis (CAPA).Results17 (29.3%) of the 58 critically ill patients were diagnosed with CAPA, of which 10 (58.82%) patients were Probable CAPA and 7 (41.18%) patients were Possible CAPA. Among this Aspergillus strains, Aspergillus fumigatus strains were found in 13 cases (76.47%) and Aspergillus niger strains in 4 cases (23.53%). 7 (41.18%) patients had concomitant bacterial fungal infections with a mortality rate of 57.14% (4/7), of which Acinetobacter baumannii was the most common pathogen. Among the patients with CAPA, galactomannan assay of bronchoalveolar lavage fluid (BALF) was performed in 5 patients with a 100% (5/5) positivity rate, and two or more serum galactomannan (GM) assays were performed in 17 patients, with a probability of favorable results in both cases of 41.2% (7/17). The 60-day mortality rate in patients with CAPA was 52.9% (9/17), whereas the non-CAPA patients had a 60-day mortality rate of 24.4% (10/41), which was statistically different (P = 0.035). Diabetes mellitus (P = 0.018, OR: 5.040 (95% CI: 1.314-19.337)), renal insufficiency (P=0.002, OR: 11.259 (95% CI: 2.480-51.111)), chronic obstructive pulmonary disease (COPD) (P = 0.003, OR: 6.939 (95% CI: 1.963-24.531)), elevated interleukin-6 (IL-6) (P = 0.022, OR: 4.160 (95% CI: 1.226 14.113)), mechanical ventilation (P = 0.002, OR: 8.100 (95%CI: 2.132 30.777)), increased duration of steroids use (P = 0.022, OR: 1.071 (95%CI: 1.010 1.135)), increased cumulative dose of steroids use ((P < 0.001, OR: 1.012 (95%CI: 1.009 1.015)), use of tocilizumab (P = 0.020, OR: 11.480 (95%CI: 2.480 51.111)), and increased length of hospitalization in ICU (P = 0.021, OR: 1.038 (95% CI: 1.006 to 1.071)), and increase in the type of antibiotics used (P = 0.002, OR: 1.603 (95% CI: 1.181 to 2.176)) were the risk factors for the occurrence of fungal infections, whereas the use of steroids or not, the use of baricitinib or not, and hypertension did not have a significant effect on the occurrence of fungal infections (P > 0.05). Patients with CAPA had a higher mortality rate, and their hospitalization was prolonged compared to non-CAPA patients. The all-cause mortality rate for patients with CAPA was 52.9%. We also performed univariate and multivariate analyses of potential factors associated with mortality, including the use of mechanical ventilation (P = 0.040 OR: 10.500, (95% CI: 1.115 to 98.914)), advanced age (P = 0.043 OR: 1.212, (95% CI: 1.006 to 1.460)), and a significantly higher CRP level (P = 0.042 OR: 1.043, (95% CI: 1.002 1.078)) had a worse prognosis. Steroids use, gender, and diabetes mellitus were not associated with patient death (P > 0.05).